Impact of allergic rhinitis on the day-to-day lives of children: insights from an Australian cross-sectional study. Issue 11 (24th November 2020) - Bosnic-Anticevich, Sinthia; Smith, Peter; Abramson, Michael; Hespe, Charlotte Mary; Johnson, Menai; Stosic, Rodney; Price, David B
Abstract : Study design and objective: Cross-sectional, observational survey to describe the impact of allergic rhinitis (AR) on Australian children (2 to 15 years). Methods: Participants (n=1541), parents of children aged 2 to 15 years, provided information on behalf of themselves and one eligible child in their household using a custom-built online questionnaire. Children were allocated to case (AR) or control (No AR) analysis groups based on a validated screening questionnaire. Statistical methods: The study sample was stratified on age: primary analysis population (6 to 15 years, n=1111; AR=797, No AR=314); exploratory population (2 to 5 years). The primary endpoint, parent-perceived burden, was quantified using a validated measure of health status and analysed via comparison of means. Results: The majority of AR cases were treated (730/797; 90.3%) and classified as having moderate-severe, intermittent AR (549/797; 68.9%). Half reported adequate symptom control in the prior 2 weeks (389/797; 48.8%; OR=4.04; 95% CI (CI) 2.24 to 7.31). Having AR was associated with worse overall health status (7.4 vs 8.4, mean difference (least squares mean difference (LSMD))=−0.99; 95% CI −1.18 to −0.79), fewer days being happy (22.2 vs 25.9, LSMD=−3.68; 95% CI −4.82 to −2.54) and more days of poor physical (2.82 vs 0.78, LSMD=2.04; 95% CI 1.61 to 2.47) and emotional (2.14 vs 0.67, LSMD=1.47; 95% CI 1.02 to −1.92) health compared with not having AR. All of these outcomes were significantly (p<0.05) worse in children who reported inadequate symptom control. Having AR negatively impacted on schoolwork, sleep and other activities, and increased the likelihood of having comorbidities. Conclusion: The parent-perceived burden of AR in Australian children is high and it impacts many areas of day-to-day living. Inadequate symptom control is a key driver of the extent of this impact. Opportunities to optimise the management of AR in children include the adoption of self-assessment tools to gauge and monitor adequacy of symptom control.